The potential of fatty acids and their derivatives as antifungal agents: a review - Guimarães, Ana Cristina Silva Esperança (2022)
Fungal contamination presents several problems: in humans, health issues arise from infections with opportunistic filamentous fungi and yeast, while in food, fungi cause spoilage and, in particular, in the case of mycotoxigenic fungi, can cause serious health issues. Several types of fatty acids and their derivatives, oxylipins, have been found to have inhibitory effect towards fungal growth and the production of mycotoxins. The use of fatty acids as antifungals could fulfil consumer’s requests of more natural and environmentally friendly compounds, while being less likely to promote fungal resistance. In addition, due to their nature, fatty acids are easily used as food additives. In this work, we review the most relevant and recent studies on the antifungal ability of fatty acids. We focused on saturated fatty acids, unsaturated fatty acids, and oxylipins, their different impact on fungal inhibition, their proposed modes of action, and their ability to impair mycotoxin production. Applications of fatty acids as antifungals and their limitations are also addressed.